15‐Year trends in respiratory care of extremely preterm infants: Contributing factors and consequences on health and growth during hospitalization. Issue 8 (30th April 2020) - Habas, Flora; Durand, Sabine; Milési, Christophe; Mesnage, Renaud; Combes, Clémentine; Gavotto, Arthur; Picaud, Jean‐Charles; Cambonie, Gilles
Abstract: Objectives: To review 15‐year trends in respiratory care of extremely preterm infants managed in a tertiary perinatal center; to identify the factors contributing to their evolution; and to determine whether these changes had an impact on infant mortality, severe morbidity, and growth. Methods: Retrospective cohort study of infants born at 23 to 26 weeks' gestation between 2003 and 2017. Changes in respiratory care were assessed in three 5‐year periods. Logistic regression was used to examine the factors associated with prolonged duration (ie, greater than the median) of invasive mechanical ventilation (IMV), noninvasive ventilation (NIV), and overall respiratory support (ORS), and those associated with adequate weight and head circumference growth. Results: Of the 396 actively treated neonates, 268 (68%) survived to discharge. Between the first and third periods, IMV duration decreased from 22 (6‐37) to 4 (1‐14.0) days ( P < .001), that of NIV increased from 24 (14‐34) to 56 (44‐66) days ( P < .001), and that of ORS from 50 (34‐68) to 63 (52‐77) days ( P < .001). Study period (2003‐2007 vs 2013‐2017) was the main factor associated with prolonged IMV ( P < .001). Use of high‐flow nasal cannula was the main factor associated with prolonged NIV ( P = .02) and ORS ( P = .02). NIV duration was associated with adequate postnatal weight ( P = .003) and head circumference ( P = .03) growth. Severe morbidities in survivors, including bronchopulmonary dysplasia, and survival at hospital discharge were comparable across the study periods. Conclusions: Respiratory management was characterized by a marked reduction in IMV. NIV withdrawal protocols are necessary to limit ORS duration while respecting postnatal growth requirements.